2020
DOI: 10.1038/s41561-019-0527-z
|View full text |Cite
|
Sign up to set email alerts
|

Complex evolving patterns of mass loss from Antarctica’s largest glacier

Abstract: Pine Island Glacier has contributed more to sea level rise over the last four decades than any other glacier in Antarctica. Model projections indicate that this will continue in the future but at conflicting rates. Some models suggest that mass loss could dramatically increase over the next few decades, resulting in a rapidly growing contribution to sea level, and fast retreat of the grounding line, where the grounded ice meets the ocean. Other models indicate more moderate losses. Resolving this contrasting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…These glaciers are particularly vulnerable to collapse because they have retrograde slopes and are grounded well below sea level (Pattyn, 2018). Such a collapse may already be underway at Thwaites Glacier (Joughin et al, 2014; Waibel et al, 2018) and, although Pine Island may have recently stabilized (Bamber & Dawson, 2020; Medley et al, 2014), it remains at risk for further future unstable retreat. As the catchment area of these and connected glaciers contains ice that would raise globally averaged sea level by 1.2 m (Rignot et al, 2019) and provide a pathway to much larger losses (>2.5 m, Martin et al, 2019), understanding the processes that contribute to (or mitigate) their instability is essential to assessing the impact of future changes.…”
Section: Introductionmentioning
confidence: 99%
“…These glaciers are particularly vulnerable to collapse because they have retrograde slopes and are grounded well below sea level (Pattyn, 2018). Such a collapse may already be underway at Thwaites Glacier (Joughin et al, 2014; Waibel et al, 2018) and, although Pine Island may have recently stabilized (Bamber & Dawson, 2020; Medley et al, 2014), it remains at risk for further future unstable retreat. As the catchment area of these and connected glaciers contains ice that would raise globally averaged sea level by 1.2 m (Rignot et al, 2019) and provide a pathway to much larger losses (>2.5 m, Martin et al, 2019), understanding the processes that contribute to (or mitigate) their instability is essential to assessing the impact of future changes.…”
Section: Introductionmentioning
confidence: 99%
“…While spaceborne observations indicate that this acceleration has levelled off recently (Rignot et al, 2019), they also support model projections suggesting modest changes in mass balance, i.e. the resulting net ice loss after accounting for all loss and gain processes, for the next decades to come (Bamber and Dawson, 2020). The dynamic ice loss is mainly responsible for the negative mass balance of Pine Island Glacier (PIG).…”
Section: Introductionmentioning
confidence: 53%
“…Based on our analysis of Sentinel and Landsat satellite images, there is no obvious indication of recent changes in the surface morphology in these areas. Either significant and wide-spread changes in the thermal and mechanical properties have occurred beneath the surface, or the observed speed-up and thinning in these areas, as previously reported by Bamber and Dawson (2020), cannot be convincingly attributed to changes in the rate factor.…”
Section: Changes In the Rate Factor And Basal Slipperiness Between Years 1996 And 2016mentioning
confidence: 72%
“…Evidence from indirect observations have indicated that changes in ice shelf thickness have occurred since at least some decades before the 1970s (Jenkins et al, 2010;Smith et al, 2017;Shepherd et al, 2004;Pritchard et al, 2012). Within the last two decades, thinning of the grounded ice (Shepherd et al, 2001;Pritchard et al, 2009;Bamber and Dawson, 2020), intermittent retreat of the grounding line (Rignot et al, 2014), changes in calving front position (Arndt et al, 2018) and the partial loss of ice shelf integrity (Alley et al, 2019) have all been reported in considerable detail. At the same time, numerical simulations of ice flow have confirmed the strong link between ice-shelf thinning, which reduces the buttressing forces, and the increased discharge across the grounding line (Schmeltz et al, 2002;Payne et al, 2004;Favier et al, 2014;Arthern and Williams, 2017;Reese et al, 2018;Gudmundsson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation